Mobility and health sector development in China and India - Holdaway, J; Levitt, P; Rajaram, N; Fang, J (Elsevier, 2015)
China and India are both attempting to create comprehensive healthcare systems in the context of rapid but uneven economic growth and rapidly changing burdens of disease. While in each country the referencing of international policies and work experience abroad have been part of this process, research has yet to examine the kind of knowledge that is exchanged or the various actors involved in knowledge circulation. Based on a study of two sub-national contexts, this article focuses on the role Chinese and Indian health professionals who have studied and worked overseas play in introducing ideas and practices about healthcare provision and health education. We found that experience abroad influenced individuals, institutions, and each society differently and with some contradictory effects. International experience clearly contributed to personal growth and led individuals to support the adoption of new institutional practices, such as more egalitarian relations between doctors and patients and between students and teachers. However, the content of what individuals learned overseas and the mechanisms through which this knowledge was introduced back into homeland settings often reinforced rather than ameliorated institutional hierarchies and social inequalities. While the scope of this research was limited, we suggest that more explicit analysis of the role professional migrants play in transferring ideas and practices within the health sector would be valuable for policymakers and funders seeking to support a more productive interaction between local and global knowledge.